A mental model approach applied to R&D decision-making. (1st January 2000) - Vislosky, D.M.; Fischbeck, P.S.
A mental model approach is developed to map systematically an organisation's R&D project-selection decision process from the cognitive beliefs of its key decision-makers. Respondents' revealed decision-criteria maps are judged against a normative project-selection model to reveal systematic departures from rational choice. The methodology is demonstrated within an industrial R&D organisation of a large production company. The results highlight the value of the mental model approach applied to R&D decision-making. Application of the methodology may prove useful to managers and policy-makers by providing insightful information about an industry's R&D selection process.